1990
DOI: 10.1093/infdis/161.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporium inflatum: Clinical Spectrum of a Newly Recognized Pathogen

Abstract: The clinical course of 11 patients is reported: a newly-described species, Scedosporium inflatum, was isolated from each. Infections were primarily focally invasive and involved musculoskeletal tissues. All but one followed penetrating trauma, often minor, or surgery. Two cases, one fatal, occurred in immunosuppressed patients. In only one case was there presumptive hematogenous spread. In three cases colonization with S. inflatum could not reliably be distinguished from infection. In vitro susceptibility test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 3 publications
2
98
0
1
Order By: Relevance
“…Osteomyelitis, septic arthritis, or wound infections usually occur when barriers are breached secondary to trauma or surgery (253,297). There have been numerous reports of infections in immunocompetent individuals, including osteomyelitis, discitis, and arthritis (95,145,155,245,268,409,443,476), usually following deep extension of local disease. Among immunocompromised hosts, bone and articular involvement is more likely to be secondary to hematogenous dissemination of the fungus (242).…”
Section: Ii) Extrapulmonary Infections (A) Cutaneous and Subcutaneoumentioning
confidence: 99%
“…Osteomyelitis, septic arthritis, or wound infections usually occur when barriers are breached secondary to trauma or surgery (253,297). There have been numerous reports of infections in immunocompetent individuals, including osteomyelitis, discitis, and arthritis (95,145,155,245,268,409,443,476), usually following deep extension of local disease. Among immunocompromised hosts, bone and articular involvement is more likely to be secondary to hematogenous dissemination of the fungus (242).…”
Section: Ii) Extrapulmonary Infections (A) Cutaneous and Subcutaneoumentioning
confidence: 99%
“…Clinical discussion (see Clinical Syndromes and Their Management below) will be limited to S. prolificans, as related species have been extensively reviewed elsewhere (153) and may not reveal phaeoid hyphae in tissue, in contrast to the case for S. prolificans. Infection with this organism is of major concern in all settings due to its refractoriness to antifungal therapy and associated high mortality (18,29,76,96,119,153,312,475,538,664,802,806). A recent review of 162 cases reported in the literature summarizes major risk factors as malignancy (46%), cystic fibrosis (12%), and solid organ transplantation (9%) and chief clinical presentations as disseminated infection (44%) and pulmonary mycoses (29%), followed by bone and joint infections (10%) (638).…”
Section: Microascalesmentioning
confidence: 99%
“…The therapeutic approach for patients with S. apiospermum or S. prolificans infections involves complete surgical resection of the lesion with or without antifungal therapy, whose role is uncertain (12,37). Infections caused by S. apiospermum have been treated with amphotericin B (35), miconazole, ketoconazole (38), itraconazole (29), and voriconazole (11), with variable clinical responses.…”
mentioning
confidence: 99%